2017
DOI: 10.1186/s13195-017-0262-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood pressure and Alzheimer disease measured up to 27 years prior to diagnosis: the HUNT Study

Abstract: BackgroundA lot of attention has been paid to the relationship of blood pressure and dementia because epidemiological research has reported conflicting evidence. Observational data has shown that midlife hypertension is a risk factor for cognitive decline and dementia later in life, whereas there is evidence that low blood pressure is predictive in later life. The aim of the present study was to examine the association between dementia and blood pressure measured up to 27 years (mean 17.6 years) prior to ascer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 44 publications
(48 reference statements)
2
57
0
1
Order By: Relevance
“…37,38 However, this assumption is complicated by the fact that different studies will find opposing results when examining the same cardiometabolic abnormality. For instance, some studies have found that abdominal obesity, 11 hypertension, 39 and high lipids 11,35 are protective against risk of dementia. Other studies find that obesity, 40,41 hypertension, 42 diabetes, 43 and high lipids 44 are risk factors for incident dementia.…”
Section: Supporting Information Table B)mentioning
confidence: 99%
“…37,38 However, this assumption is complicated by the fact that different studies will find opposing results when examining the same cardiometabolic abnormality. For instance, some studies have found that abdominal obesity, 11 hypertension, 39 and high lipids 11,35 are protective against risk of dementia. Other studies find that obesity, 40,41 hypertension, 42 diabetes, 43 and high lipids 44 are risk factors for incident dementia.…”
Section: Supporting Information Table B)mentioning
confidence: 99%
“…While the literature is inconsistent about the risk of AD associated with hypertension in individuals over age 60 (6871), studies indicate that elevated systolic blood pressure (SBP) (≥ 160 mm Hg) in midlife is associated with an increased risk of eventual AD (68, 72, 73). Hypertension has also been associated with an increased risk of AD and cognitive decline in APOE ε4 carriers compared to non-carriers (74, 75).…”
Section: Ad Comorbidity Considerationsmentioning
confidence: 99%
“…Our ndings may indicate that this discrepancy is due to the different effects of SBP and DBP on dementia. Inverse associations of SBP with the risk of AD have been reported in large, population-based health studies [39], and recently supported by a Mendelian randomization study of AD [40]. Although SBP cannot fully represent su ciency of cerebral blood ow, SBP is negatively associated with AD incidence, which could suggest su cient cerebral oxygen levels follow insu cient cerebral blood ow.…”
Section: Discussionmentioning
confidence: 86%